PERSEPSI ANALIS KREDIT / PEMBIAYAAN TENTANG RESIKO KREDIT PADA BANK KONVENSIONAL DAN BANK SYARIAH (STUDIKASUS PADA BANK CENTRAL ASIA DAN BANK SYARIAH MANDIRI) - Samiah Harhara; Sofyan S Harahap (Media Riset Akuntansi, Auditing & Informasi, 2009)
A number of theories on Islamic accounting have been proposed in the study on Islamic accounting. It has been showed that there is a require for Moslem business organization to have a different accounting that build successful for Muslim, not only in this life but also for hereafter. This study attempts to elaborate the perception on credit analysis in Islamic banking and in conventional banking in Jakarta. There are three hypotheses that has been examined. The result shows that there is no significant perception difference among the two on "process of risk management application " and "credit risk identification " but in the 3rd identification test, it was found a significant difference perception on "appearing stagnant credit". Although the means are not significantly different, the descriptive statistics shows that the perception of credit analysts in Islamic banking is more pragmatic towards Islamic Accounting issues rather than those in conventional accounting.Keywords: Credit analysts, conventional bank, Islamic bank, accounting information.Islamic perspective.